2013
DOI: 10.1155/2013/382184
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hepatic Delivery of Drugs: Novel Strategies and Their Significance

Abstract: Liver is a vital organ responsible for plethora of functions including detoxification, protein synthesis, and the production of biochemicals necessary for the sustenance of life. Therefore, patients with chronic liver diseases such as viral hepatitis, liver cirrhosis, and hepatocellular carcinoma need immediate attention to sustain life and as a result are often exposed to the prolonged treatment with drugs/herbal medications. Lack of site-specific delivery of these medications to the hepatocytes/nonparenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 155 publications
1
60
0
Order By: Relevance
“…Repeated attempts have been made to deliver drugs specifically to HCC via ASGPR because of their high affinity and rapid internalization in hepatic tumor cells. 11,13,14 Recent researches demonstrated that Lf might be a potential HCC ligand because of its specific binding with ASGPR. 14,[19][20][21] And Lf exhibits its active targeting ability for HCC cells by the ASGPR endocytosis process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Repeated attempts have been made to deliver drugs specifically to HCC via ASGPR because of their high affinity and rapid internalization in hepatic tumor cells. 11,13,14 Recent researches demonstrated that Lf might be a potential HCC ligand because of its specific binding with ASGPR. 14,[19][20][21] And Lf exhibits its active targeting ability for HCC cells by the ASGPR endocytosis process.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14 Recent researches demonstrated that Lf might be a potential HCC ligand because of its specific binding with ASGPR. 14,[19][20][21] And Lf exhibits its active targeting ability for HCC cells by the ASGPR endocytosis process. 14,[19][20][21] Our previous work also confirmed the HCC-targeting effect of PLS modified with Lf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of NR1H3 agonists into differentiation cocktails might also be beneficial for the generation of functional hepatocyte-like cells from other stem cell resources and for further studies of hepatocyte transplantation in end-stage liver disease. Finally, it is also possible to accelerate liver regeneration in vivo by liver-specific target delivery of NR1H3 agonists, such as to package agonists into liver-specific vehicles [54,55].…”
Section: Discussionmentioning
confidence: 99%